ETUDE COMPARATIVE DES PARAMÈTRES MORPHO-PONDERAUX CHEZ DEUX GENOTYPES DE POULET (SÉLECTIONNÉ ET LOCAL) ESTIMATION DES CORRELATIONS - HADJOUDJ, Saber (My University, 2016)
Local breeds are an important tool for rural development and fight against poverty. This study is to describe the morpho-weight characteristics of two genetic types of chicken (commercial strain and local breed). A total of 60 roosters (30 for each genotype) from the region of Mazouna (W. Relizane) were used in this study. Industrial genotype shows its superiority (P <0.05) for all traits measured except for leg length and height of the ridge. In the industrial strain, the live weight appears to be moderately related to body length and scale (r = 0.40 and 0.36; P <0.05). From local roosters, by cons, no correlation was raised between the morphoweight parameters. In both groups, body weight was significantly correlated with the carcass weight with varying intensity (r = 0.75 and r = 0.93, P <0.001). A moderate relationship (r = 0.37, P <0.05) between liver weight and that of the heart was observed in the industrial genotype.
Keywords: poulet local; souche commerciale; poids; organes internes; corrélations phénotypiques; Local chicken; commercial strain; weight; internal organs; phenotypic correlations